Evaluation of umbilical cord blood hematological parameters in pregnant women with fetal growth restriction - Demir, Mustafa Bertan; Ak, Mehmet; Dağlıtuncezdi Çam, Şeyma; Cündübey, Cevat Rifat (The European Research Journal, 2023)
Objectives: The present study attempted to evaluate the relationship between fetal growth restriction (FGR) and the platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) in singleton term pregnancy. Methods: We carried out this prospective, case-control study at a Training and Research Hospital in Türkiye between May 2021 and January 2023. We utilized ultrasonography to assess singleton pregnancy with FGR between 37-40 weeks of gestation and considered the patients’ last menstrual periods (LMD). Results: We recruited 250 pregnant women in the study and divided them into the FGR (n = 125) and healthy control (n = 125) groups. Our findings revealed no significant difference between the groups by age, body mass index (BMI), stillbirth history, abortion, tobacco use, and regular pregnancy monitoring (p > 0.05). Fetal birth weights and hospitalization in the neonatal intensive care unit (NICU) were also similar between the groups. Yet, 1- and 5-minute APGAR scores were significantly lower in the FGR group than in the control group. In addition, compared to the healthy subjects, the FGR group had significantly increased white blood cell, lymphocyte, neutrophil, platelet counts and NLR and PLR values, but mean platelet volume (MPV) remained similar. Conclusions: In a nutshell, our findings suggested that two noteworthy inflammatory markers, NLR and PLR, are likely to elevate in the presence of FGR.